Pengaruh Komunikasi Pemasaran Terhadap Keputusan Pembelian Handbody Lotion Citra Ditinjau Dari Undang-Undang Perlindungan Konsumen - Hia, Niscaya; Sarah, Eva Margareth; Rolando Marpaung (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2023)
Citra Handbody Lotion is currently widely used for community needs. Citra Handbody users are increasing due to the very rapid development of technology today. Likewise, pricing strategies influence purchasing decisions. The purpose of this research is to determine the influence of marketing communications on purchasing decisions for Citra Handbody Lotion among management study program students at Sari Mutiara University, Indonesia in terms of consumer protection laws. Apart from maintaining product quality, marketing communications are maintained by the company so that people remain loyal to their products. A company needs to create a consumer protection system that contains elements of legal certainty and information disclosure as well as access to information. The approach used in this research is survey research because it takes samples from one population and takes a sample size of 73 respondents who are students of the management study program at Sari Mutiara Indonesia University using the Slovin formula. Data obtained using a questionnaire. The results of this research show that the marketing communication variable (X) has a significant positive effect on the purchasing decision variable (Y). The data was processed statistically using SPSS 26 program tools.